The Practice of General Data Protection Regulations Fine and Penalty on Google Inc. vs CNIL Case - Maskun; Rian Nugraha (International Journal of Law and Public Policy, 2020)
The development of technology on this era is bringing two side on the humanity which is the positive and negative side. On the positive side, the technology could help human to finding information easily from their device (e.g smartphone), while on the other side this techonology could bring harm on privacy side. There fore, with those harm, the concept of privacy is vital. On European Union where they have concern toward the personal data with General Data Protection Regulation (GDPR). On the GDPR, European Union have their own rule about the right of erasure, it also known as the right to be forgotten (RTBF) which written on Article 17. This article has it own problem due to the scope of application. On may 2015 the French Commission Nationale de l’informatique et libertés (CNIL) served a formal notice on google if individual asking about the remvoval of links to web page from the list of result displayed following a search performed on that individual name etc. Google have to apply that removal on all google domain (google.com) and not remove it just in the google local domain (google.fr). Due to the difference of perspective toward the Article 17 of General Data Protection Regulation, google wont remove it on the google main domain (google.com), and so on march 2016 (CNIL) found that google failed to comply the formal notice and imposed a penalty of €100.000 and so google sought to have the adjudication annulled. 11 September 2018, the European Court of Justice hearing this case where it is about the territorial scope of European data protection law. But then on 24 September 2019, Court of Justice held that the right to be forgotten on the article 17 doesn’t require google to de-list search result on all of its domains, however google still required to de-list the result on the all of the European Union domain. The purpose of this study to analyze wether the court opinion and decision toward the google.inc v CNIL case. On other side it will also determine wether the European Union data protection law could be applied outside the European Union or not.